Betalain rich functional extract with reduced salts and nitrate content from red beetroot (Beta vulgaris L.) using membrane separation technology. (15th January 2017) - Mereddy, Ram; Chan, Adeline; Fanning, Kent; Nirmal, Nilesh; Sultanbawa, Yasmina
Highlights: Betalain is the major purplish red pigment in the red beetroot ( Beta vulgaris L.). Membrane technology successfully removed 99% turbidity from the juice. More than 95% of salts and nitrate were removed after three difiltration. The total betalain content in BRE was increased up to 46%. Membrane technology can be the potential green technology for beetroot juice industries. Abstract: An initial laboratory-scale evaluation of separation characteristics of membranes with nominal molecular weight cut-offs (NMWCO) ranging from 30 kD down to 0.5 kD indicated effective separation of betalains in the 0.5 kD region. Subsequent pilot-level trials using 1 kD, loose reverse osmosis (LRO) and reverse osmosis (RO) spiral-wound membranes showed LRO membrane to be very efficient with up to 96% salt and 47% other dissolved solids removed while retaining majority of the pigment (∼98%) in the betalain rich extract (BRE). The total betalain content in the BRE increased up to 46%, the highest recovery reported so far at pilot scale level. Interestingly, more than 95% of the nitrates were removed from the BRE after the three diafiltrations. These studies indicate that membrane technology is the most efficient technique to produce BRE with highly reduced amounts of salts and nitrate content.